Optimalisasi Dana Pemerintah Kepada Lembaga Bantuan Hukum Untuk Mendukung Keadilan Bagi Masyarakat Miskin di Daerah Jawa Timur - Amelia, Shelomita Putri; Fransisca R. N, Tabitha; Cantiqa, Shevanna Putri; Alzahrah, Aurelya Putri; Wicaksana, Mikie Aditya; Yuli, Yuliana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Legal aid is an effort to help people who are not well-off in the legal field. Indonesian people, especially the underprivileged, consider legal aid as a form of legal protection. The formulation of the problem in this journal is how the role of legal aid institutions in increasing the availability and accessibility of legal aid for the poor in East Java, how to optimize government funds for legal aid institutions in order to create justice for the poor in East Java. The research method used is the normative juridical method with a statutory approach and a case approach. This research focuses more on analyzing the laws and regulations relating to the legal issues being addressed. The results found are that local governments can play an active role in supporting the legal aid budget for the poor, in accordance with the Legal Aid Law Article 19 Paragraph (1) and Paragraph (2). Strategic action is needed to improve the efficiency of legal aid to the poor and improve their access to justice. The provision of legal aid to the poor should be a top priority, by addressing issues that impede provision through planned actions. Efforts to improve access to justice for the poor in East Java should be directed at optimizing government funding for legal aid institutions. By doing so, it is expected to create an environment